Dendrobium huoshanense C.Z.Tang et S.J.Cheng: A Review of Its Traditional Uses, Phytochemistry, and Pharmacology - Gao, Leilei; Wang, Fang; Hou, Tingting; Geng, Chunye; Xu, Tao; Han, Bangxing; Liu, Dong (Frontiers in Pharmacology, 2022)
Dendrobium huoshanense, a traditional medicinal and food homologous plant, belongs to the family Orchidaceae and has a long history of medicinal use. It is reported that the stem of D. huoshanense has a variety of bioactive ingredients such as polysaccharides, flavonoids, sesquiterpenes, phenols, etc. These bioactive ingredients make D. huoshanense remarkable for its pharmacological effects on anti-tumor, immunomodulation, hepatoprotective, antioxidant and anticataract. In recent years, its rich pharmacological activities have attracted extensive attention. However, there is no systematic review focusing on the chemical compositions and pharmacological effects of D. huoshanense. Therefore, the present review aims to summarize current research on the chemical compositions and pharmacological activity of D. huoshanense. This study provides valuable references and promising ideas for further investigations of D. huoshanense.